2016
DOI: 10.1177/2057158516635480
|View full text |Cite
|
Sign up to set email alerts
|

Health dialogue with non-native-speaking parents: Child health nurses’ experiences

Abstract: The aim of this study was to explore child health care nurses' experiences of conducting health dialogues with non-nativespeaking parents. In Sweden, it is not routine that all non-native-speaking parents are invited to a health dialogue. Regardless of language and cultural background, it is important that all parents have the same opportunities to participate. The data were obtained through two focus-group interviews and analysed using qualitative content analysis. The results revealed one theme Need for cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
1
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
1
1
0
2
Order By: Relevance
“…The HCPs described this work as diverse and complex. This is in line with other studies of experiences of THDs among child healthcare nurses and school nurses [26][27][28]. In addition, the HCPs in this study claimed that the complex work with THDs demands high competence and the right skills when it comes to using the pedagogical tool, the knowledge of diseases, the ability to answer questions, and the ability to set goals together with the individual.…”
Section: Discussionsupporting
confidence: 90%
“…The HCPs described this work as diverse and complex. This is in line with other studies of experiences of THDs among child healthcare nurses and school nurses [26][27][28]. In addition, the HCPs in this study claimed that the complex work with THDs demands high competence and the right skills when it comes to using the pedagogical tool, the knowledge of diseases, the ability to answer questions, and the ability to set goals together with the individual.…”
Section: Discussionsupporting
confidence: 90%
“…Det foreligger derimot lite forskning rettet spesifikt mot mødre med innvandrerbakgrunn og deres opplevelser fra det første møte med helsesykepleier på hjemmebesøk. Flere studier (13)(14)(15)(16) fremhever behovet for videre forskning på feltet. Sjetne, Kjøllesdal, Iversen og Holmboe (13) sin rapport om brukererfaringer med svangerskaps-, fødsels-og barselomsorgen i Norge fra 2013 viser at mødre med innvandrerbakgrunn var mindre fornøyde med hjemmebesøkstilbudet av helsesykepleier etter fødsel sammenlignet med norske mødre.…”
Section: Bakgrunnunclassified
“…Forfatterne påpeker behov for mer forskning innenfor det flerkulturelle møtet mellom helsesykepleiere og foreldre (15). Johansson, Golsäter og Hedberg (16) belyser at helsesykepleiers flerkulturelle kompetanse er av stor betydning for å oppnå målet om å gi likeverdige tjenester til alle brukere.…”
Section: Bakgrunnunclassified
“…They showed cognitive skills in applying their knowledge in a PA plan, which helped them to structure different life problems; this is in line with other studies [ 22 , 23 ]. Still other studies, taking health literacy into consideration, have shown that health-promoting work in which the knowledge and understanding of the importance of PA – which can be appraised and applied in people’s lives– is essential to achieve different health goals such as PA recommendations [ 17 , 18 , 43 ]. Another study among middle-aged women showed the importance of knowing how to perform PA; they did not perform PA because they did not know how to do it [ 44 ].…”
Section: Discussionmentioning
confidence: 99%